A new mycorrhizal species of Ceratobasidium (Ceratobasidiaceae) associated with roots of the epiphytic orchid Gomesa recurva from Brazilian Atlantic Forest - Da S. Cruz, Everaldo; Freitas, Emiliane F. S.; Da Silva, Meiriele; L. Pereira, Olinto; M. Kasuya, Maria C. (Phytotaxa, 2022)
Species from Ceratobasidium are known as orchid mycorrhizal, plant pathogens or saprophytic. In mycorrhizal association with orchids, Ceratobasidium can establish a highly specific interaction. Gomesa recurva is an epiphytic orchid occurring in the Brazilian Atlantic Forest. In the present study mycorrhizal fungi were isolated from roots of G. recurva and its phylogenetic positions was investigated. A total of nine isolates were obtained directly from pelotons and submitted to phylogenetic analysis based on alignments of sequences of the internal transcribed spacer (ITS) of the nuclear ribosomal DNA. Phylogenetic analyzes, along with morphological data, revealed that isolates are distinct from all known Ceratobasidium species and a new species, namely Ceratobasidium gomesae sp. nov., is proposed. Given the dependence on mycorrhizae for germination and protocorm development, knowledge about orchid symbionts is an important factor in managing the conservation of these plants, and future studies may investigate the ability of C. gomesae to promote seed germination.